2016
DOI: 10.1590/0102-6720201600s10006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Roux-en-Y Gastric Bypass on Body Weight and Clinical Metabolic Comorbidities in Bariatric Surgery Service of a University Hospital

Abstract: Background: Due to the high failure rate observed in the clinical treatment of morbid obesity an increase in bariatric surgery indications, as an alternative for the control of obesity and comorbidities, is noticeable. Aim: To evaluate the performance of type 2 diabetes mellitus, high blood pressure and dyslipidemia in patients submitted to Roux-en-Y gastric bypass in late follow-up. Methods:Retrospective analysis of 59 patients included in the bariatric surgery program. Anthropometric (height and body weight)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
7
0
2
Order By: Relevance
“…In the analysis of quality of life using the BAROS protocol, the present study and the studies by Castanha et al 21 , Silva et al 22 and Silva et al 23 , which investigated samples with similar mean age, demonstrated an improvement in quality of life, despite being different types of study. Even studies with very different methodologies, such as the one by Sarwer et al 16 , found an improvement in the quality of life.…”
Section: Discussionsupporting
confidence: 59%
“…In the analysis of quality of life using the BAROS protocol, the present study and the studies by Castanha et al 21 , Silva et al 22 and Silva et al 23 , which investigated samples with similar mean age, demonstrated an improvement in quality of life, despite being different types of study. Even studies with very different methodologies, such as the one by Sarwer et al 16 , found an improvement in the quality of life.…”
Section: Discussionsupporting
confidence: 59%
“…Consistently, several studies have shown the efficacy of bariatric surgery in the various comorbidities associated with obesity. A retrospective study of 59 patients evaluated the evolution of Type II Diabetes Mellitus, systemic arterial hypertension and dyslipidemia after Roux-en-Y gastroplasty using anthropometric (height and weight) and laboratory data (low density lipoprotein, high density lipoprotein, triglycerides and glycemia) in the pre-and postoperative periods (mean time 7±3 years) 25 . The study showed that after surgery, 40% of patients continued to be treated for systemic arterial hypertension and that remission of diabetes (81%) and dyslipidemia (94%) had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these data are consistent with the literature. A study with 160 patients submitted to Roux-en-Y Gastric Bypass (Fobi-Capella), identified through the BAROS protocol that 60.6% of the patients evaluated the quality of life as "excellent", 26.8% as "very good", 9.8% as "good" and 2.8% as "bad" 25 . Another study, using BAROS in 70 patients, showed that the highest proportion of patients presented a "good" quality of life (50%), followed by "acceptable" (35.8%), "very good" (12.8%) and "insufficient" (1.4%) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…RYGB continues to demonstrate sustained long‐term weight‐loss results as well as improvement and resolution of ORCs, such as GERD, CVD, degenerative joint disease, T2D, OSA, HTN, pulmonary disease, and psychiatric disease . In addition to weight loss and comorbid disease improvement/resolution, both RYGB and SG were further validated as durable bariatric surgeries with significant improvement in patient‐reported outcomes based on quality‐of‐life scores .…”
Section: Executive Summarymentioning
confidence: 99%